THE IMPACT OF CHANGES IN BANK INDONESIA'S INTEREST RATE POLICY ON THE LIQUIDITY OF CONVENTIONAL COMMERCIAL BANKS - Zulkifli Ramadhan; Febriyanti, Zahara; Rahmawati, Putri; Lestari, Ayu; NurHalimah, Siti; Nur Oktavia, Andini; Feriskinanti, Pamesti Ajeng; Juniarti, Nola Tri (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
This study aims to examine the impact of Bank Indonesia's interest rate policy on customer savings decisions regarding choosing savings products in conventional banks, as well as its effect on the liquidity of these banks. The research utilizes a literature review method with a qualitative descriptive approach. The results and discussion indicate that the offered interest rates by conventional banks significantly influence customer behavior in selecting savings products. Changes in interest rates can affect customers' inclination to save in banks and consequently impact the liquidity of conventional banks. Other factors that influence customer decisions include product promotions, service quality, and customer preferences. While changes in Bank Indonesia's interest rate policy can affect customer loyalty to banks, customer preferences in choosing savings products are also influenced by other non-interest rate-related factors. This study provides an in-depth understanding of the impact of interest rate changes on the liquidity of conventional banks, offering valuable insights for Bank Indonesia and conventional banks in formulating effective policies to maintain financial sector stability and foster sustainable economic growth.